Learners’ Written Interaction Effect on Learners’ Academic Achievement in Chemistry. - Irungu, Mwangi Newton; Grace, Nyagah; Mercy, Mugambi (Advances in Social Sciences Research Journal, 2019)
This article purposed to establish the Learners’ Written Interaction Effect on Learners’ Academic Achievement in Chemistry. The study generated two null hypotheses: H01: There is no statistically significant learner’s written interaction effect on learners’ academic achievement in Chemistry. HO2: There is no statistically significant relationship between learner’s written interaction effect and learners’ academic achievement in Chemistry. Qualitative and quantitative mixed methods research design approach was adopted for the study. simple and stratified sampling was used to select 32 public secondary schools as the sample population for the study. Data was collected using five research instruments: Chemistry Achievement Test (CAT), Observation check list (OCL), Students’ Questionnaire (SQ), Document Analysis Guide (DAG) and Student Discussion Guide (SDG). To ensure reliability and validity of the CAT, questions from Kenya Certificate of Secondary Education past papers were selected. Pearson Product-Moment Correlation Coefficient was used to test the reliability of the (SQ) while the DAG and SDG instruments were validated during the pilot study. Quantitative data was analyzed using inferential and descriptive statistics while thematic analysis was used to analyze qualitative data. The results of simple regression analysis revealed no statistically significant learners’ written interaction effect on learners’ academic achievement in chemistry while Pearson Product-Moment Correlation Coefficient revealed a weak, linear and negative weak relationship (r = -0.2234) between learners’ written interaction effect and learners’ academic achievement in Chemistry.